2016
DOI: 10.1016/j.cryobiol.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and reproduction of an Antarctic tardigrade retrieved from a moss sample frozen for over 30 years

Abstract: Long-term survival has been one of the most studied of the extraordinary physiological characteristics of cryptobiosis in micrometazoans such as nematodes, tardigrades and rotifers. In the available studies of long-term survival of micrometazoans, instances of survival have been the primary observation, and recovery conditions of animals or subsequent reproduction are generally not reported. We therefore documented recovery conditions and reproduction immediately following revival of tardigrades retrieved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…tolerance (Yamaguchi et al, 2012;Tanaka et al, 2015;Hashimoto et al, 2016;Boothby et al, 2017). In addition to its capability of entering anhydrobiosis, A. antarcticus is also able to tolerate freezing of its habitat through cryobiosis (Altiero et al, 2015), as also demonstrated by the survival of specimens after more than 30 years of storage at -20°C within a frozen moss sample (Tsujimoto et al, 2016). These two cryptobiotic capabilities, together with a short life cycle and reproduction via thelytokous parthenogenesis (Altiero et al, 2015), allow A. antarcticus to synchronize growth and reproduction with favourable environmental conditions, and to persist in habitats where conditions can change unpredictably even within the same day, such as the Antarctic ponds in which it lives.…”
Section: Desiccation Tolerancementioning
confidence: 98%
“…tolerance (Yamaguchi et al, 2012;Tanaka et al, 2015;Hashimoto et al, 2016;Boothby et al, 2017). In addition to its capability of entering anhydrobiosis, A. antarcticus is also able to tolerate freezing of its habitat through cryobiosis (Altiero et al, 2015), as also demonstrated by the survival of specimens after more than 30 years of storage at -20°C within a frozen moss sample (Tsujimoto et al, 2016). These two cryptobiotic capabilities, together with a short life cycle and reproduction via thelytokous parthenogenesis (Altiero et al, 2015), allow A. antarcticus to synchronize growth and reproduction with favourable environmental conditions, and to persist in habitats where conditions can change unpredictably even within the same day, such as the Antarctic ponds in which it lives.…”
Section: Desiccation Tolerancementioning
confidence: 98%
“…Currently, approximately 1200 species have been reported from various habitats, such as marine, fresh-water, or limno-terrestrial environments, though the real number of tardigrade species is estimated to be much higher [4,5]. Tardigrades were found in harsh environments such as Antarctica as well as in urban area, e.g., from activated sludge in a sewage treatment plant [6,7,8]. All tardigrades require surrounding water to grow and reproduce, but some limno-terrestrial species are able to tolerate almost complete dehydration.…”
Section: Tardigrades As Model Animals Tolerant To Various Extreme mentioning
confidence: 99%
“…It was proved before that they undergo several morphological changes like tun formation or glass like dried structure formation due to desiccation. 10 But what was the factor that helped them to rehydrate and bring back to life still remained a mystery.…”
Section: Tardigrades In Low Temperaturementioning
confidence: 99%